Analysis of Abrasion of Hot Metal Powder Spray Coated Layer - Balogh, Gábor; Pálinkás, Sándor; Bodzás, Sándor; Fazekas, Lajos; Molnár, András (International Journal of Engineering and Management Sciences, 2020)
By the application of the tradicional overhead welding and the different powder coating technologies results a new surface with improved abrasion resistance, we can optimize the dimensions of the part or we can rebuild some surface as a kind of repairing technology. By application of this technology we can avoid the replacement of the total expensive parts of the structure. Opposite to the tradicional overhead welding in this case there will be diffusion connection between the raw material and the surface coating, this connection type shows several positive properites. Our goal is to investigate the abrasion resistance of the coating. In this article we would like to introduce our results of the abrasion test by apllication of different powder coatings.